4.2k views
4 votes
Simplify into one fraction. -1/x-9 - -2/x+7

a. 1/(x-9)(x+7)
b. -3/(x-9)(x+7)
c. x-25/(x-9)(x+7)
d. -3x+11/(x-9)(x+7)

User Peralmq
by
5.8k points

2 Answers

3 votes


\bf -\cfrac{1}{x-9}-\cfrac{-2}{x+7}\implies -\cfrac{1}{x-9}+\cfrac{2}{x+7}\implies \cfrac{2}{x+7}-\cfrac{1}{x-9}\impliedby \stackrel{\textit{our LCD is}}{(x+7)(x-9)} \\\\\\ \cfrac{(x-9)2~~-~~(x+7)1}{(x+7)(x-9)}\implies \cfrac{2x-18~~-~~x-7}{(x+7)(x-9)}\implies \cfrac{x-25}{(x+7)(x-9)}

User Gavin Jackson
by
5.2k points
2 votes

Answer: I think c but I am not sure

Step-by-step explanation: Hope this helps

User Daremachine
by
4.9k points